Human umbilical cord blood-derived stem cells and brain-derived neurotrophic factor protect injured optic nerve：viscoelasticity characterization - Lv, Xue-man; Liu, Yan; Wu, Fei; Yuan, Yi; Luo, Min (Neural regeneration research, 2016)
The optic nerve is a viscoelastic solid-like biomaterial.Its normal stress relaxation and creep properties enable the nerve to resist constant strain and protect it from injury.We hypothesized that stress relaxation and creep properties of the optic nerve change after injury.Moreover,human brain-derived neurotrophic factor or umbilical cord blood-derived stem cells may restore these changes to normal.To validate this hypothesis,a rabbit model of optic nerve injury was established using a clamp approach.At 7 days after injury,the vitreous body received a one-time injection of 50 μg human brain-derived neurotrophic factor or 1 × 106 human umbilical cord blood-derived stem cells.At 30 days after injury,stress relaxation and creep properties of the optic nerve that received treatment had recovered greatly,with pathological changes in the injured optic nerve also noticeably improved.These results suggest that human brain-derived neurotrophic factor or umbilical cord blood-derived stem cell intervention promotes viscoelasticity recovery of injured optic nerves,and thereby contributes to nerve recovery.